Better together: synergy in nanocellulose blends. (25th December 2017) - Mautner, Andreas; Mayer, Florian; Hervy, Martin; Lee, Koon-Yang; Bismarck, Alexander
Abstract : Cellulose nanopapers have gained significant attention in recent years as large-scale reinforcement for high-loading cellulose nanocomposites, substrates for printed electronics and filter nanopapers for water treatment. The mechanical properties of nanopapers are of fundamental importance for all these applications. Cellulose nanopapers can simply be prepared by filtering a suspension of nanocellulose, followed by heat consolidation. It was already demonstrated that the mechanical properties of cellulose nanopapers can be tailored by the fineness of the fibrils used or by modifying nanocellulose fibrils for instance by polymer adsorption, but nanocellulose blends remain underexplored. In this work, we show that the mechanical and physical properties of cellulose nanopapers can be tuned by creating nanopapers from blends of various grades of nanocellulose, i.e. (mechanically refined) bacterial cellulose or cellulose nanofibrils extracted from never-dried bleached softwood pulp by chemical and mechanical pre-treatments. We found that nanopapers made from blends of two or three nanocellulose grades show synergistic effects resulting in improved stiffness, strength, ductility, toughness and physical properties. This article is part of a discussion meeting issue 'New horizons for cellulose nanotechnology'.